Experimental infection with Tritrichomonas suis in heifers - Cobo, Eduardo Ruben (2001)
Nine heifers were intravaginally challenged with 9.3 × 106 Tritrichomonas suis reference strains. Vaginal mucus and serum samples were collected weekly 4 weeks post-inoculation. Vaginal mucus was cultured for T. suis and sera was tested by ELISA against whole cell antigens for T. suis and Tritrichomonas foetus. All vaginal mucus cultures were T. suis-negative during the experiment. ELISA values for both antigens were similar and differences were not significant (P > 0.05). Positive control serum samples from one heifer vaccinated against T. foetus showed anti-T. suis ELISA values. We concluded that T. suis intravaginal inoculation induced a low level of serum immune response in heifers measured by ELISA and both protozoa probably share a common antigen. However, under the experimental conditions of this trial, colonization of the heifers' genital tract was not possible in any of the nine animals. © 2001 Elsevier Science B.V.